2012
DOI: 10.1586/erp.12.67
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavior therapy via the Internet: a systematic review of applications, clinical efficacy and cost–effectiveness

Abstract: Internet-based cognitive behavior therapy (ICBT) is a promising treatment that may increase availability of cognitive behavior therapy (CBT) for psychiatric disorders and other clinical problems. The main objective of this study was to determine the applications, clinical efficacy and cost-effectiveness of ICBT. The authors conducted a systematic review to identify randomized controlled trials investigating CBT delivered via the internet for adult patient populations. Searches to identify studies investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
440
3
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 614 publications
(482 citation statements)
references
References 130 publications
23
440
3
16
Order By: Relevance
“…Our results are not in line with findings from earlier systematic reviews evaluating the cost effectiveness of Internet‐based treatments (Donker et al., 2015; Hedman et al., 2012). The authors of previous studies concluded that Internet‐based treatments have high probability of being cost effective compared to controls for various mental health problems including depression (Donker et al., 2015; Hedman et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results are not in line with findings from earlier systematic reviews evaluating the cost effectiveness of Internet‐based treatments (Donker et al., 2015; Hedman et al., 2012). The authors of previous studies concluded that Internet‐based treatments have high probability of being cost effective compared to controls for various mental health problems including depression (Donker et al., 2015; Hedman et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The authors of previous studies concluded that Internet‐based treatments have high probability of being cost effective compared to controls for various mental health problems including depression (Donker et al., 2015; Hedman et al., 2012). Other authors, however, stated that the information they had was not sufficient to draw firm conclusions (Andersson, Wagner, & Cuijpers, 2016; Arnberg, Linton, Hultcrantz, Heintz, & Jonsson, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations